Advances in Genome Editing With CRISPR Systems and Transformation Technologies for Plant DNA Manipulation - Nadakuduti, Satya Swathi; Enciso-Rodríguez, Felix (Frontiers in Plant Science, 2021)
The year 2020 marks a decade since the first gene-edited plants were generated using homing endonucleases and zinc finger nucleases. The advent of CRISPR/Cas9 for gene-editing in 2012 is a major science breakthrough that revolutionized both basic and applied research in various organisms including plants and consequently honored with “The Nobel Prize in Chemistry, 2020”. CRISPR technology is a rapidly evolving field and multiple CRISPR-Cas derived reagents collectively offer a wide range of applications for gene-editing and beyond. While most of these technological advances are successfully adopted in plants to advance functional genomics research and development of innovative crops, others await optimization. One of the biggest bottlenecks in plant gene-editing has been the delivery of gene-editing reagents, since genetic transformation methods are only established in a limited number of species. Recently, alternative methods of delivering CRISPR reagents to plants are being explored. This review mainly focuses on the most recent advances in plant gene-editing including 1) the current Cas effectors and Cas variants with a wide target range, reduced size and increased specificity 2) cytosine, adenine and glycosylase base editors that can precisely install all possible transition and transversion mutations in target sites 3) prime editing that can directly copy the desired edit into target DNA by search and replace method and 4) CRISPR delivery mechanisms for plant gene-editing that bypass tissue culture and regeneration procedures including de novo meristem induction, delivery using viral vectors and prospects of nanotechnology-based approaches.